Investigating a Singapore-Based Mathematics Textbook and Teaching Approach in Classrooms in England - Lindorff, Ariel Mariah; Hall, James; Sammons, Pamela (Frontiers in Education, 2019)
The high mathematics performance of pupils in Singapore on international assessments has prompted educational initiatives in other countries – such as the UK and the USA – to adopt Singapore-based approaches in an attempt to raise mathematics achievement. Empirical evidence to support the transferability of such approaches beyond the Singaporean context, however, is limited. This article reports findings from a mixed methods Cluster Randomized Controlled Trial (mmCRCT) evaluating the use of a primary mathematics textbook series and teaching approach in England based on a textbook and teaching approach from Singapore. Main features of the intervention included textbook use, mixed-ability groups, use of manipulatives, and emphasis on mastery (i.e. ensuring all pupils grasp core concepts before proceeding to new topics). A delayed treatment experimental design was used within the mmCRCT, with 12 schools randomly allocated into two groups. The experimental group used the textbooks and teaching approach from September 2015. The delayed treatment control group proceeded with “business as usual” until January 2016, then started using the textbooks and teaching approach. Data were collected (in the first, second and third terms of one school year) on pupils’ mathematics knowledge and skills, pupils’ attitudes towards mathematics, classroom practice (based on structured observation schedules and qualitative field notes), teacher perspectives (from semi-structured interviews), and intervention-specific professional development (in July 2015 for the experimental group, December 2015 for the delayed treatment control group, observed by researchers and followed by focus-group interviews). Results showed a small but significant positive effect by Term 3 of using the mastery-oriented materials and approach from September on pupils’ subsequent mathematics knowledge and skills, but no persistent difference between groups across terms on their attitudes. Differences in classroom practice between the two groups were observed in the first term but insignificant by the third term. Qualitative findings elaborate on and illustrate these first-term differences, teachers’ perspectives on their practice, variations in textbook use and teaching approach implementation, and considerations of fidelity to intervention. Implications are drawn for policy and practice in mathematics teaching and for research using mixed methods experimental designs to evaluate a combination of processes, perspectives and outcomes.